Influence of Cylindrical Electrode Configuration on Plasma Parameters in a Sputtering System - Bard, Alaa Khamees; Abbas, Qusay Adnan (Iraqi Journal of Science, 2022)
In the present work, the effect of the cylindrical configurations of the sputtering device electrodes on the plasma parameters (Debye length, electron temperature, electron density, plasma frequency) is studied. Also, the effect of the argon gas pressure on the discharge properties is examined with gas pressures of (0.08, 0.2, 0.4 and 0.6) Torr. The properties of the plasma are diagnosed by optical emission spectrometry. The spectroscopic method is adopted for examining the atomic spectra of argon emission.  The electron temperature is determined by the Boltzmann method. While, the Stark-widening method was employed for calculating the electron number density. The voltage against current curves of the cylindrical sprayer discharges shows the voltage to be nearly constant with slight increase in current. An increase in pressure causes the cathode cascades to compress and the negative glow to become thinner and more luminous. Plasma properties such as electron temperature and Debye length  decrease with increasing pressure, while electron number density and plasma frequency increase.